Bartter-like syndrome caused by kanamycin during therapy for multidrug-resistant Mycobacterium tuberculosis - Chothia, Mogamat-Yazied; Esser, Jan H; de Vries, Nihal; Davids, Mogamat Razeen (African Journal of Nephrology, 2018)
Multidrug-resistant Mycobacterium tuberculosis infection (MDR-TB) is a highly prevalent communicable disease in South Africa and often occurs in those with HIV infection. We describe three HIV-infected patients with pulmonary MDR-TB who received treatment with a regimen that included kanamycin and subsequently developed a Bartter-like syndrome. The clinical presentation varied from asymptomatic to severely symptomatic electrolyte disturbances, with one fatal outcome. This report highlights the importance of the routine monitoring of electrolytes in MDR-TB patients receiving treatment that includes kanamycin.